2008
DOI: 10.1198/004017007000000470
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Problems With Normal Approximation Confidence Intervals for Probabilities

Abstract: Although it is well known that modern methods of computing confidence intervals (CIs) based on likelihood or simulation have important advantages, normal approximation confidence interval procedures (NACPs) are still widely used, especially in the analysis of censored data. This is because CIs from NACPs are easy to compute and easy to explain. But when the sample size is not large or when there is heavy censoring, the performance of NACPs can be poor. A transformation can be applied to keep CI endpoints from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, if the SE is large, this CI might not be within the range (0, 1). Instead of the obvious corrective method of pruning the CI to the known range (0, 1), we consider an appropriate transformation method in the following, which was particularly developed for CIs for probabilities (see Hong et al 2008).…”
Section: Wald-type Confidence Interval For F â (T)mentioning
confidence: 99%
“…However, if the SE is large, this CI might not be within the range (0, 1). Instead of the obvious corrective method of pruning the CI to the known range (0, 1), we consider an appropriate transformation method in the following, which was particularly developed for CIs for probabilities (see Hong et al 2008).…”
Section: Wald-type Confidence Interval For F â (T)mentioning
confidence: 99%
“…Applying Gauss-Hermite quadrature gives 15) where n k2 is the number of quadrature points, q 2,k2 are the evaluation points and w 2,k2 are the weights. The evaluation points are the roots of the Hermite polynomial of degree n k2 , H n k2 (q 2 ), and the weights are…”
Section: Gauss-hermite Quadrature Is a Numerical Integration Techniqumentioning
confidence: 99%
“…They observed that their growth estimator produces intervals that are longer and more variable than the normal approximation. In the censored data context, Hong et al (2008) pointed out that the normal approximation to confidence interval calculations can be poor when the sample size is not large or there is heavy censoring. In the context of approximation of the binomial distribution, Chang et al (2008) made similar observations.…”
Section: Introductionmentioning
confidence: 99%